2018
DOI: 10.1002/jcb.27373
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mechanism based study on disinfectants against multidrug‐resistant Acinetobacter baumannii

Abstract: Acinetobacter baumannii has emerged as a hospital-acquired pathogen and has spread in the hospital settings, leading to enhanced nosocomial outbreaks associated with high death rates. Therefore, the aim of the current study is to determine the effective concentration of disinfectants like sodium hypochlorite, hydrogen peroxide, and chlorine dioxide, against multidrug-resistant (MDR) strains of A. baumannii. In this study, we have investigated the effect of disinfectants on different MDR strains i.e. RS307, RS6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 63 publications
0
20
1
Order By: Relevance
“…40 One study revealed that the incidence of MDRAB was addressed by controlling the inappropriate duration of antimicrobial treatments and the misuse of carbapenems. 41 However, the values of DDD in our study are clearly higher than those reported in Australia and the Netherlands. 21,42 This may be related to the insufficient of administration of antibiotic application.…”
Section: Discussioncontrasting
confidence: 80%
“…40 One study revealed that the incidence of MDRAB was addressed by controlling the inappropriate duration of antimicrobial treatments and the misuse of carbapenems. 41 However, the values of DDD in our study are clearly higher than those reported in Australia and the Netherlands. 21,42 This may be related to the insufficient of administration of antibiotic application.…”
Section: Discussioncontrasting
confidence: 80%
“…S10). This might be associated with the fact that disinfectant itself could also pose direct effects on the cell membrane, as reported in a previous study [53].…”
Section: Discussionmentioning
confidence: 61%
“…Consequently, the quenching of ROS may eliminate the antibacterial effects of chloramine and free chlorine. Previous studies also show that microbial ROS production potentiates antibacterial effects [52], and that chlorine-based disinfectants cause a ROS-dependent damage mechanism [53]. However, it should be admitted that there is much controversy about whether ROS changes are symptoms or causes of the increased HGT and antimicrobial induced killing of bacteria [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Reports showed that chlorhexidine have role in ROS elevation to produce its antimicrobial effect [1921]. Therefore, the reactive oxygen species (ROS) was measured by nitro blue tetrazolium assay (NBT) on a multi-well scanning spectrophotometer (ELISA reader) as per published protocol [22].…”
Section: Methodsmentioning
confidence: 99%
“…MDA (the secondary product) produce a pink-colored dimeric compound with thiobarbituric acid (TBA), which can be easily quantified using ELISA reader. We have quantified lipid peroxidation as per our published method [22].…”
Section: Methodsmentioning
confidence: 99%